FREE POLIO IMMUNIZATION MOVEMENT: EFFORTS TO PREVENT POLIO DISEASE IN TODDLER IN RW 05, CILANDAK, SELATAN JAKARTA - Syamsiah, Siti; Nabilah, Nabilah (International Journal of Engagement and Empowerment (IJE2), 2025)
This study evaluates the effectiveness of a free polio vaccination program in RW 05, Cilandak Subdistrict, with a focus on analyzing factors influencing community participation rates. The research employed an exploratory qualitative approach, with data collected through: (1) in-depth discussions with 18 caregivers of toddlers, (2) direct observation of 5 healthcare workers during program implementation, and (3) analysis of supporting documents. The evaluation results indicated a significant increase in vaccination coverage, from 65% in the previous year to 82% during the study period. This success was primarily supported by: (1) active data collection by local health cadres, (2) evidence-based visual communication strategies, and (3) a personalized approach in community education. Identified challenges included: (1) concerns about side effects (reported by 37% of respondents), (2) limited healthcare infrastructure, and (3) community-level misconceptions. A critical finding revealed that individual counseling approaches successfully improved vaccine acceptance in 60% of initially hesitant cases. The study recommends: (1) strengthening the capacity of cadres in health risk communication, (2) optimizing family-based information systems, and (3) innovating service models that are adaptive to the needs of working communities.